Efficacy of the Novel Medical Adhesive, MAR-VIVO-107, in an Acute Porcine Liver Resection Model. (October 2017) - Tanaka, Hirokazu; Fukushima, Kenji; Srinivasan, Pramod Kadaba; Pawlowsky, Kerstin; Koegel, Babette; Hata, Koichiro; Ku, Yonson; Uemoto, Shinji; Tolba, René H.
Background . Despite modern surgical techniques, insufficient hemostasis after liver trauma is still a major cause of morbidity and mortality after injury. Therefore, efficient hemostatic agents are indicated. In this study, we evaluated the hemostatic efficacy of a novel synthetic wound adhesive (MAR-VIVO-107) based on polyurethane/polyurea, compared with a widely used fibrin adhesive (Tisseel). Materials and Methods . Twelve German Landrace pigs were randomly assigned to 2 groups. The animals were operated under sterile conditions. A midline laparotomy was performed and the left liver lobe was isolated and resected, using a surgical scissor, in order to induce hepatic trauma. MAR-VIVO-107 or Tisseel was applied to the resected area. The animals were monitored for 60 minutes; thereafter, they were sacrificed under anesthesia. Blood and tissue samples were collected pre- and postresection for biochemical and hematological analyses. Results . MAR-VIVO-107 versus Tisseel (mean ± SD, P value)—postsurgical survival rate was 100% in both groups. Bleeding time was significantly higher in Tisseel compared with MAR-VIVO-107 (10.3 ± 5.0 vs 3.7 ± 1.5 minutes, P = .0124). In trend, blood loss was less in the MAR-VIVO-107 group (54.3 ± 34.9 vs 105.5 ± 65.8 g, P = .222). Aspartate transaminase levels were significantly lower in the MAR-VIVO-107 group when compared with the Tisseel group (39.0 ± 10.0 vs 72.4 ± 23.4 U/L, P = .0459). Conclusion . The efficacy of MAR-VIVO-107 and comparable performance to the gold standard fibrin have been shown under pre-clinical conditions. MAR-VIVO-107 permits hemorrhage control within seconds, even in wet environment.